Ulises en un mar de tinta : obra periodística de Eduardo Zalamea Borda - Zalamea Borda, Eduardo, 1907-1963 (Colección Séneca., 2015)
Essays and poetry written by Eduardo Zalamea Borda (Ulises) and published in honor of the centenary of his birth.